Young Consumers' Insights on Brand Equity: Effects of Brand Association, Brand Loyalty, Brand Awareness, and Brand Image - Hudiono, Rini (Institut Pariwisata dan Bisnis Internasional, 2022)
One of the consequences of shopping is that consumers only pay attention to certain brands that can satisfy their needs and desires. Therefore the organization must pay attention to ways to follow and further develop a positive brand image. The purpose of this study was to examine and analyze the effect of brand association, brand loyalty, brand awareness and brand image on brand equity in young consumers. The sample in this study were several university students in the Surakarta environment. The sampling method used in this study is non-probability sampling, while the technique used is purposive sampling. Data collection method in this study is surveys using a Likert Scale. The independent variables in this study consisted of brand association, brand loyalty, brand awareness, and brand image. The independent variable in this study is brand equity. The results of data from several respondents were analyzed using descriptive statistical tests and multiple linear regression using the Statistical Package of the Social Science Computer Program (SPSS) version 21. The results through multiple linear regression analysis showed that brand associations and brand loyalty had an effect on brand equity of premium travel destinations in Labuan Bajo on social media among young consumers while brand awareness and brand image, have no effect on brand equity in social media among young consumers.